Kriteria Cek dan Bilyet Giro dalam Transaksi Bisnis yang Menimbulkan Konsekuensi Hukum Pidana dan Perdata - Ferdy Saputra (Universitas Medan Area, 2019)
In the use of checks and bilyet giro as collateral for debt which results in legal consequences, both in the form of criminal law and civil law, checks and bilyet giro as bank products are closely related to banking law. The link is due to the fact that state and private banks are the parties that issue checks and bilyet giro. As a result of the use of checks and demand deposits that develop within the community, banks as issuers of checks and giro checks are often made to participate in legal issues carried out by their customers. Bank participation in legal matters, at a minimum, provides Investigators with information about checking accounts on behalf of their customers. Therefore, it is necessary to regulate the banking sector which regulates the use of checks and bank notes, specifically on what usage criteria can be categorized as criminal acts, and vice versa which use criteria can be categorized as private / civil legal relations